Pemberdayaan UMKM Desa Mekar Sari melalui Pelatihan Digital Marketing Sederhana - Taufik, Muhammad Irham; Herlina, R Lisye; Rizkia, Adinda; Hatta, A Feriansyah; Ramdani, Eka; Putri, Diana Amelia; Faujiah, Dian; Larasati, Fitriana Daeni; Gania, Friska (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
MSMEs play a crucial role in the national economy, yet many rural entrepreneurs still face limitations in utilizing digital marketing. This community service program was conducted in Mekar Sari Village, Ngamprah Sub-district, West Bandung Regency, aiming to enhance MSME capacity in applying digital marketing strategies. The methods included needs assessment, training, mentoring, and evaluation. The training materials covered creating online stores on marketplaces, developing social media content, utilizing WhatsApp Business with product catalogs, as well as basic skills in product photography and simple design. The results showed significant achievements: 100% of participants created online stores, 80% independently uploaded social media content, 90% implemented WhatsApp Business with product catalogs, and all participants produced product photos and simple designs. These findings align with previous studies emphasizing the importance of digital marketing in supporting MSME sales and sustainability. Thus, simple and practical digital training proved effective in strengthening MSME independence and expanding market reach.